Real-world evidence on the benefits of optimal itch relief and skin clearance in atopic dermatitis management: a study from the TARGET-DERM AD registry - Jonathan I. Silverberg; Brian M. Calimlim; Ayman Grada; Christopher G. Bunick; Melinda J. Gooderham; Vivian Y. Shi; Chibuzo Obi; Keith D. Knapp; Breda Munoz; Julie M. Crawford; Amy S. Paller (Journal of Dermatological Treatment)
Background: In atopic dermatitis (AD), the real-world impact of achieving itch and skin lesion treatment targets compared to partial improvement remains unclear.Objective: We assessed the relationship between itch relief (reduction in Worst Itch Numeric Rating Scale [WI-NRS]) and skin clearance (Investigator Global Assessment [IGA] 0/1) with other patient-reported outcomes.Methods: Using TARGET-DERM AD registry data on adults receiving standard-of-care treatment, we described and modeled the relationship of itch severity (Worst Itch Numeric Rating Scale [WI-NRS]) and skin lesion severity (IGA) outcomes with patient-reported (quality of life ([DLQI)], AD severity [(POEM]), sleep ([Sleep-NRS]), and skin pain [(Pain-NRS]).Results: Among 1,920 participants (58.6% female; 54.5% Non-Hispanic White; 93.8% US; mean age 45 years), ideal outcomes (DLQI 0/1, POEM 0-2, Sleep-NRS 0/1, and Pain-NRS 0/1) were most frequent for those achieving the optimal targets for itch (WI-NRS 0/1; 52.1%, 53.7%, 57.3%, and 83.1%, respectively) and skin clearance (IGA 0/1; 44.7%, 44.3%, 44.7%, and 74.3%, respectively). The odds ratios of ideal outcomes were greatest for participants with complete or near-complete resolution of both itch and skin (DLQI 0/120.0; POEM 0-2: 41.7; Sleep-NRS: 16.1; Pain-NRS: 6.0).Conclusions: Achieving optimal treatment targets for both itch and skin lesion improvement markedly enhances patient-reported AD outcomes. The results of this study support using minimal disease activity criteria to assess therapeutic effectiveness.